Sitotoksisitas Kombinasi Seng-oksida dan Ekstrak Curcuma longa Terhadap Fibroblas Gingiva Manusia - Vina Aprilia; Asti Meizarini; Titien Hary Agustantina (Jurnal Material Kedokteran Gigi, 2019)
The use of zinc oxide - eugenol as periodontal dressing is controversial due to the toxic nature of eugenol and Curcuma longa Linn as a safe natural herbal, is expected to replace eugenol function. Previous research has proven that the combination of zinc oxide with Curcuma liquid extract has an antibacterial properties and the use of those as wound dressing through in vivo studies proved to accelerate wound healing. The ingredients applied to the oral cavity must benon-toxic and biocompatible, therefore cytotoxicity testing 1 is required. To determine the cytotoxicity of zinc oxide and Curcuma longa extract combination on human gingival fibroblast cells. Cytotoxicity test of combination of zinc oxide powder with Curcuma liquid extract was done at ratio of 1: 1 (group A) and 2: 1 (group B), Curcuma liquid extract (group C) and zinc oxide powder (group D), which performed on human gingival fibroblast culture-cells (3-5x103 densities) in 96 wells microplate. MTT essay was used to analyzed with IC50 parameters. Statistical analysis using oneway Anova and LSD. The number of living cells in group A = 64.819%, group B = 59.452%, group C = 52.859% and group D = 60.502%. There was no significant difference between the groups of A, B, D but those groups were significantly different to group C. Combination of zinc oxide with Curcuma extract ratio of 1: 1 and 2: 1, zinc oxide powder and Curcuma liquid extract are not toxic to human gingival fibroblast at IC50.